Zoned three-way conversion catalyst comprising platinum, palladium and rhodium
By designing a combination of partitioning architecture and PGM-free outer coating in TWC catalyst, the problem of low thermal stability of Pt/Pd/Rh catalyst during high-temperature aging is solved, and the control effect of HC and NOx emissions is improved. Excellent in cold start and phosphorus toxicity resistance.
Patent Information
- Application Number
- CN202380044448.0
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Priority Date
- 2022-06-02
- Filing Date
- 2023-06-01
- Publication Date
- 2025-01-14
AI Technical Summary
Conventional Pt/Pd/Rh trimetal TWC catalysts have low thermal stability during high-temperature aging, resulting in a reduced catalytic activity. Especially under harsh operating conditions, it is difficult to effectively reduce the emission of HC and NOx.
A catalyst with a partition architecture was designed, with the Pt/Rh synergistic effect in the front area improving HC performance, low carrier coating load accelerated cold start heating, and a PGM-free outer coating was added to the outside to improve phosphorus toxicity.
The emission control efficiency of the catalyst is improved, the NMHC and NOx content in the tailpipe emission is reduced, and the temperature of the catalyst is accelerated during cold start-up, enhancing the tolerance to phosphorus poisoning.
Smart Images

Figure HDA0005164853050000011 
Figure HDA0005164853050000012 
Figure HDA0005164853050000013
Abstract
Description
Technical Field
[0001] The presently claimed invention is directed to a catalyst for treating exhaust gas to reduce pollutants contained therein. In particular, the presently claimed invention is directed to a catalytic article comprising a zoned three-way conversion (TWC) catalyst comprising platinum, palladium and rhodium. Background Art
[0002] Three-way conversion (TWC) catalysts are well known for their catalytic activity in reducing pollutants such as NO, CO and HC using platinum group metals (PGMs). Conventional TWC catalysts use Pd and Rh as active catalytic components. Considering the current market prices of PGMs, replacing a portion of the more expensive palladium (Pd) with cheaper platinum (Pt) in TWC catalysts will help catalytic converter manufacturers and automobile manufacturers to significantly reduce costs. Therefore, the present invention focuses on the development of highly active, zoned TWC catalysts comprising platinum, palladium and rhodium as PGM components. It is known that replacing a large amount of Pd with Pt (e.g., 50%) in TWC catalysts generally results in lower catalytic activity, which may be due to the relatively low thermal stability of Pt to high temperature aging, especially under harsh TWC operating conditions.
[0003] Therefore, it is desirable to design Pt / Pd / Rh based TWC catalysts with appropriate architecture to improve emission control efficiency.
[0004] Purpose of the Invention
[0005] The object of the present invention is to improve the cumulative non-methane hydrocarbons (NMHC) and NOx performance of a three-way conversion (TWC) catalyst comprising Pt, Pd and Rh as active platinum group metal (PGM) components. Summary of the invention
[0006] The present invention provides a catalytic product, which includes: a) a substrate; b) a first zone coated with a first catalytic layer; and c) a second zone coated with a second catalytic layer, wherein the first catalytic layer comprises platinum supported on a cerium dioxide-zirconia mixed oxide or a cerium dioxide-alumina composite material or both; and rhodium supported on a cerium dioxide-zirconia mixed oxide, a cerium dioxide-alumina composite material, alumina or any combination thereof, wherein the second catalytic layer comprises palladium supported on a cerium dioxide-zirconia mixed oxide, alumina, a cerium dioxide-alumina composite material or any combination thereof; and rhodium supported on a cerium dioxide-zirconia mixed oxide, alumina, a cerium dioxide-alumina composite material or any combination thereof, wherein the first zone occupies the inflow end portion of the substrate, and the second zone occupies the outflow end portion of the substrate.
[0007] The present invention also provides a method for preparing a catalytic product, wherein the method includes preparing a first catalytic layer slurry comprising platinum supported on a cerium dioxide-zirconia mixed oxide or a cerium dioxide-alumina composite material or both; and rhodium supported on a cerium dioxide-zirconia mixed oxide, a cerium dioxide-alumina composite material, alumina or any combination thereof; preparing a second catalytic layer slurry comprising palladium supported on a cerium dioxide-zirconia mixed oxide, alumina, a cerium dioxide-alumina composite material or any combination thereof; and rhodium supported on a cerium dioxide-zirconia mixed oxide, alumina, a cerium dioxide-alumina composite material or any combination thereof; coating the first catalytic layer slurry on the inflow end portion of the substrate to obtain a first zone; coating the second catalytic layer slurry on the outflow end portion of the substrate to obtain a second zone; subjecting the substrate to calcination at a temperature ranging from 400°C to 700°C, wherein the step of preparing the slurry includes a technique selected from incipient wetness impregnation, incipient wetness co-impregnation and post-addition.
[0008] The invention also provides an exhaust gas treatment system for an internal combustion engine, the exhaust gas treatment system comprising a catalytic article according to the invention claimed herein. The invention further provides a method of treating a gaseous exhaust stream comprising hydrocarbons, carbon monoxide and nitrogen oxides, the method comprising contacting the exhaust stream with a catalytic article or an exhaust gas treatment system according to the invention claimed herein. BRIEF DESCRIPTION OF THE DRAWINGS
[0009] To provide an understanding of embodiments of the present invention, reference is made to the accompanying drawings, which are not necessarily drawn to scale, and in which reference numerals refer to components of exemplary embodiments of the present invention. The accompanying drawings are exemplary only and should not be construed as limiting the present invention. The above and other features of the presently claimed invention, their nature and various advantages will become more apparent when the following detailed description is considered in conjunction with the accompanying drawings:
[0010] Figure 1A A two-layer zoned catalytic article is shown (Comparative Catalysts A and B).
[0011] Figure 1B A single-layer partitioned catalytic article is shown (Comparative Catalyst C).
[0012] Figure 1C A single-layer partitioned catalytic article of the inventive catalyst D according to the present invention is shown.
[0013] Figure 1D A single-layer partitioned catalytic article of the inventive catalyst E according to the invention is shown.
[0014] Figure 1E A partitioned catalytic article having an outer coating free of PGMs is shown for inventive catalyst F according to the present invention.
[0015] Figure 2 Engine exhaust and catalyst bed temperatures are shown for the catalyzed articles.
[0016] Figure 3 Comparative cumulative non-methane hydrocarbon (NMHC) and NOx tailpipe emissions according to the FTP-75 test cycle using the catalytic articles are presented.
[0017] Figure 4A is a perspective view of a honeycomb type substrate support that may include a catalyst composition according to one embodiment of the invention claimed herein.
[0018] Figure 4B is relative to Figure 4A Zoom in and follow the Figure 4A A partial cross-sectional view taken through a plane of the end surface of a substrate carrier, showing Figure 4A An enlarged view of the multiple gas flow channels shown in FIG.
[0019] Figure 5 is relative to Figure 4A A cross-sectional view of an enlarged section, where Figure 4A The honeycomb-type substrate in ref. 3 represents a wall-flow filter substrate monolith. DETAILED DESCRIPTION
[0020] The presently claimed invention will be described more fully below. The presently claimed invention can be embodied in many different forms and should not be construed as limited to the embodiments described herein; rather, these embodiments are provided to make the presently claimed invention more complete and complete, and to fully convey the scope of the invention to those skilled in the art. Language in this specification should not be construed to indicate that any non-claimed element is essential to the practice of the materials and methods of the present disclosure.
[0021] Unless otherwise specified herein or clearly contradicted by context, all methods described herein can be performed in any suitable order. Unless otherwise stated, the use of any and all examples or exemplary language (e.g., "such as") provided herein is intended only to better illustrate materials and methods and is not intended to limit the scope.
[0022] definition :
[0023] The terms "a," "an," and "the" and similar referents used in the context of describing the materials and methods discussed herein (especially in the context of the following claims) are to be construed to cover both the singular and the plural, unless otherwise indicated herein or clearly contradicted by context.
[0024] Recitation of ranges of values herein are merely intended to serve as a shorthand method of referring individually to each separate value falling within the range, unless otherwise indicated herein, and each separate value is incorporated into the specification as if it were individually recited herein.
[0025] In the context of the present invention, the term "washcoat" is used interchangeably for "first catalytic layer and / or second catalytic layer" which form a first zone and a second zone, respectively, on a portion of a substrate. As used herein, the term "washcoat" has its usual meaning in the art, i.e., a thin, adherent coating of a catalytic material or other material applied to a substrate material. Typically, the washcoat is formed by preparing a slurry of particles containing a certain solid content (e.g., 15 wt%-60 wt%) in a liquid vehicle, which is then applied to a substrate and dried to provide a washcoat layer.
[0026] The term "overcoat" is used interchangeably with "topcoat" or "top washcoat" or "second layer", and the overcoat is deposited on at least a portion of the first zone.
[0027] In the context of the present invention, the term "first zone" is used interchangeably for "inlet zone" or "front zone", and the term "second zone" is used interchangeably for "outlet zone" or "rear zone". The terms "first zone" and "second zone" also describe the relative positioning of the catalytic article in the flow direction, and the relative positioning of the catalytic article when placed in the exhaust gas treatment system, respectively. The first zone will be positioned upstream, while the second zone will be positioned downstream. The first zone covers at least some portion of the substrate from the inlet of the substrate, while the second zone covers at least some portion of the substrate from the outlet of the substrate. The inlet of the substrate is the first end (inflow end portion) capable of receiving the flow of the engine exhaust flow from the engine, and the outlet of the substrate is the second end (outflow end portion) from which the treated exhaust flow leaves.
[0028] The term "three-way conversion catalyst" or TWC catalyst refers to a catalyst that simultaneously promotes a) the reduction of nitrogen oxides to nitrogen and oxygen; b) the oxidation of carbon monoxide to carbon dioxide; and c) the oxidation of unburned hydrocarbons to carbon dioxide and water.
[0029] The term "NOx" refers to nitrogen oxide compounds such as NO and / or NO 2 .
[0030] As used herein, the term "stream" refers broadly to any combination of flowing gases that may contain solid or liquid particulate matter.
[0031] As used herein, the terms "upstream" and "downstream" refer to the relative directions of flow of engine exhaust gas from the engine to the tailpipe, with the engine being in the upstream position and the tailpipe and any pollutant abatement articles such as filters and catalysts being downstream of the engine.
[0032] In the context of the present invention, the amount of platinum group metals (such as platinum / palladium / rhodium) and / or support materials (such as ceria-zirconia mixed oxides, ceria-alumina composites, alumina, etc.) is calculated in weight % based on the total weight of the washcoat (including an optional top washcoat) present on the substrate. That is, the amount is calculated without taking into account the amount of the substrate, although the substrate is part of the catalytic article.
[0033] The present invention focuses on addressing the low HC activity associated with conventional Pt / Pd / Rh tri-metallic TWC technology. Therefore, a Pt / Pd / Rh based TWC catalytic article with a zoned architecture is designed. The inventive design features Pt / Rh synergy in the front zone to improve HC performance, low washcoat loading to accelerate warming during cold start, and a PGM-free topcoat to improve phosphorus poisoning resistance.
[0034] Catalytic products :
[0035] The present invention provides, in a first aspect, an article comprising: a) a substrate;
[0036] b) a first region coated with a first catalytic layer; and c) a second region coated with a second catalytic layer,
[0037] wherein the first catalytic layer comprises platinum supported on a ceria-zirconia mixed oxide or a ceria-alumina composite material or both; and rhodium supported on a ceria-zirconia mixed oxide, a ceria-alumina composite material, alumina or any combination thereof,
[0038] wherein the second catalytic layer comprises palladium supported on ceria-zirconia mixed oxide, alumina, ceria-alumina composite material or any combination thereof; and rhodium supported on ceria-zirconia mixed oxide, alumina, ceria-alumina composite material or any combination thereof,
[0039] The first region occupies the inflow end portion of the substrate, and the second region occupies the outflow end portion of the substrate.
[0040] The total loading of the first catalytic layer and the second catalytic layer divided by the volume of the substrate is less than 3.2 grams per cubic inch.
[0041] Amount of platinum group metals :
[0042] Based on the total weight of the first catalytic layer and the second catalytic layer, the amount of platinum in the first catalytic layer and the second catalytic layer is preferably in the range of 0.02 wt % to 3.0 wt %. More preferably, based on the total weight of the first catalytic layer and the second catalytic layer, the amount of platinum in the first catalytic layer and the second catalytic layer is in the range of 0.05 wt % to 2.0 wt %.
[0043] Based on the total weight of the first catalytic layer and the second catalytic layer, the amount of palladium in the first catalytic layer and the second catalytic layer is preferably in the range of 0.02 wt % to 5.0 wt %. More preferably, based on the total weight of the first catalytic layer and the second catalytic layer, the amount of palladium in the first catalytic layer and the second catalytic layer is in the range of 0.05 wt % to 3.0 wt %.
[0044] Based on the total weight of the first catalytic layer and the second catalytic layer, the amount of rhodium in the first catalytic layer and the second catalytic layer is preferably in the range of 0.01 wt % to 1.0 wt %. More preferably, based on the total weight of the first catalytic layer and the second catalytic layer, the amount of rhodium in the first catalytic layer and the second catalytic layer is in the range of 0.05 wt % to 0.5 wt %.
[0045] The weight ratio of palladium to platinum in the first catalytic layer and the second catalytic layer is preferably 4: 1 to 1: 4. More preferably, the weight ratio of palladium to platinum in the first catalytic layer and the second catalytic layer is 3: 1 to 1: 3.
[0046] Preferably, the weight ratio of rhodium loaded on cerium dioxide-zirconia mixed oxide or cerium dioxide-alumina composite material or both in the first catalytic layer to rhodium loaded on cerium dioxide-zirconia mixed oxide, alumina, cerium dioxide-alumina composite material or any combination thereof in the second catalytic layer is in the range of 1.5:1 to 4:1.
[0047] Preferably, the amount of platinum in the first catalytic layer is 0.02 wt % to 3.0 wt % based on the total weight of the first catalytic layer. More preferably, the amount of platinum in the first catalytic layer is 0.02 wt % to 2.5 wt % based on the total weight of the first catalytic layer. Even more preferably, the amount of platinum in the first catalytic layer is 0.05 wt % to 2.0 wt % based on the total weight of the first catalytic layer.
[0048] Preferably, the amount of platinum loaded on the ceria-zirconia mixed oxide or the ceria-alumina composite material or both in the first catalytic layer is 60 wt % to 100 wt % based on the total weight of platinum in the first catalytic layer and the second catalytic layer. More preferably, the amount of platinum loaded on the ceria-zirconia mixed oxide or the ceria-alumina composite material or both in the first catalytic layer is 70 wt % to 100 wt % based on the total weight of platinum in the first catalytic layer and the second catalytic layer. Most preferably, the amount of platinum loaded on the ceria-zirconia mixed oxide or the ceria-alumina composite material or both in the first catalytic layer is 80 wt % to 100 wt % based on the total weight of platinum in the first catalytic layer and the second catalytic layer.
[0049] Preferably, the total amount of rhodium in the first catalytic layer is 0.01 wt % to 1.0 wt % based on the total weight of the first catalytic layer. More preferably, the total amount of rhodium in the first catalytic layer is 0.01 wt % to 0.5 wt % based on the total weight of the first catalytic layer.
[0050] Preferably, the amount of palladium is in the range of 0.02 wt % to 5.0 wt % based on the total weight of the second catalytic layer. More preferably, the amount of palladium is in the range of 0.02 wt % to 4.0 wt % based on the total weight of the second catalytic layer.
[0051] Preferably, based on the total weight of palladium in the first catalytic layer and the second catalytic layer, the amount of palladium loaded on ceria-zirconia mixed oxide, alumina, ceria-alumina composite material or any combination thereof in the second catalytic layer is preferably 50 wt % to 100 wt %. More preferably, based on the total weight of palladium in the first catalytic layer and the second catalytic layer, the amount of palladium loaded on ceria-zirconia mixed oxide, alumina, ceria-alumina composite material or any combination thereof in the second catalytic layer is 60 wt % to 100 wt %. Most preferably, based on the total weight of palladium in the first catalytic layer and the second catalytic layer, the amount of palladium loaded on ceria-zirconia mixed oxide, alumina, ceria-alumina composite material or any combination thereof in the second catalytic layer is 75 wt % to 100 wt %.
[0052] Preferably, the amount of rhodium supported on ceria-zirconia mixed oxide, alumina, ceria-alumina composite material or any combination thereof in the second catalytic layer is preferably 0 wt % to 50 wt % based on the total weight of rhodium in the first catalytic layer and the second catalytic layer. More preferably, the amount of rhodium supported on ceria-zirconia mixed oxide, alumina, ceria-alumina composite material or any combination thereof in the second catalytic layer is 0 wt % to 25 wt % based on the total weight of rhodium in the first catalytic layer and the second catalytic layer.
[0053] Carrier material :
[0054] The "support" in the catalytic material or catalyst composition or catalyst support coating refers to a material that receives metals (e.g., PGMs), stabilizers, promoters, binders, etc. by precipitation, association, dispersion, impregnation or other suitable methods, such as alumina, ceria-alumina composite materials, ceria-zirconia mixed oxides, etc.
[0055] The term "support" throughout this application has its general meaning as in the field of heterogeneous catalysis. Generally, the term "support" refers to a catalytically active substance or its corresponding precursor attached to a support material. The support material may be inert or participate in the catalytic reaction. Typically supported catalysts are prepared by impregnation or coprecipitation and optionally subsequent calcination.
[0056] Ceria-alumina composites :
[0057] Cerium dioxide-aluminum oxide composite material is CeO 2 Composite materials distributed on the surface and / or in the bulk of aluminum oxide in the form of particles and / or nanoclusters. Each oxide can have its own unique chemical and solid physical state. Surface CeO of aluminum oxide 2 The modification may be in the form of discrete parts (particles or clusters) or in the form of a ceria layer partially or completely covering the surface of the alumina.
[0058] Preferably, the amount of the ceria-alumina composite material present in the first catalytic layer and the second catalytic layer is in the range of 5.0 wt % to 80 wt % based on the total weight of the first catalytic layer and the second catalytic layer. More preferably, the amount of the ceria-alumina composite material present in the first catalytic layer and the second catalytic layer is in the range of 10 wt % to 60 wt % based on the total weight of the first catalytic layer and the second catalytic layer. More preferably, the amount of the ceria-alumina composite material present in the first catalytic layer and the second catalytic layer is in the range of 15 wt % to 40 wt % based on the total weight of the first catalytic layer and the second catalytic layer.
[0059] The CeO in the ceria-alumina composite material in the first catalytic layer or the second catalytic layer is based on the total weight of the ceria-alumina composite material in the corresponding catalytic layer. 2 The amount of (cerium dioxide) is preferably 1.0 wt% to 60 wt%. More preferably, the CeO in the ceria-alumina composite material in the first catalytic layer or the second catalytic layer is 1.0 wt% to 60 wt%, based on the total weight of the ceria-alumina composite material in the corresponding catalytic layer. 2Even more preferably, the CeO in the ceria-alumina composite material in the first catalytic layer or the second catalytic layer is 5.0 wt % to 50 wt %. Even more preferably, the CeO in the ceria-alumina composite material in the first catalytic layer or the second catalytic layer is 5.0 wt % to 50 wt % based on the total weight of the ceria-alumina composite material in the corresponding catalytic layer. 2 %. And even more preferably, CeO in the ceria-alumina composite material in the first catalytic layer or the second catalytic layer is 5.0 wt. % to 30 wt. % based on the total weight of the ceria-alumina composite material in the corresponding catalytic layer. 2 8.0 wt % to 20 wt %.
[0060] The Al in the ceria-alumina composite material present in the first catalytic layer or the second catalytic layer is based on the total weight of the ceria-alumina composite material in the corresponding catalytic layer. 2 O 3 The amount of (alumina) is preferably 40 wt % to 99 wt %. More preferably, the Al in the ceria-alumina composite material present in the first catalytic layer or the second catalytic layer is 10 wt % to 20 wt %, based on the total weight of the ceria-alumina composite material in the corresponding catalytic layer. 2 O 3 Even more preferably, the Al in the ceria-alumina composite material present in the first catalytic layer or the second catalytic layer is 50 wt % to 95 wt %. Even more preferably, the Al in the ceria-alumina composite material present in the first catalytic layer or the second catalytic layer is 50 wt % to 95 wt % based on the total weight of the ceria-alumina composite material in the corresponding catalytic layer. 2 O 3 The Al content of the ceria-alumina composite material in the first catalytic layer or the second catalytic layer is 70 wt % to 95 wt %. Most preferably, the Al content of the ceria-alumina composite material in the first catalytic layer or the second catalytic layer is 70 wt % to 95 wt %. 2 O 3 It is 80 wt % to 92 wt %.
[0061] Preferably, the average particle size of ceria in the ceria-alumina composite is less than 200 nm. More preferably, the particle size is in the range of 5.0 nm to 50 nm. The particle size is determined by transition electron microscopy.
[0062] The ceria-alumina composite material present in the first catalytic layer or the second catalytic layer may contain a dopant selected from zirconium oxide, lanthanum oxide, titanium oxide, hafnium oxide, magnesium oxide, calcium oxide, strontium oxide, barium oxide, or any combination thereof. The total amount of the dopant in the ceria-alumina composite material is preferably in the range of 0.001 wt % to 15 wt % based on the total weight of the ceria-alumina composite material in the corresponding catalytic layer.
[0063] Ceria-alumina composite material can be prepared by methods known to those skilled in the art (such as coprecipitation or surface modification). In these methods, a suitable cerium-containing precursor is contacted with a suitable aluminum-containing precursor, and then the mixture thus obtained is converted into a cerium-alumina composite material. Suitable cerium-containing precursors are, for example, water-soluble cerium salts and colloidal cerium dioxide suspensions. Ceria-alumina can also be prepared by an atomic layer deposition method, in which a cerium oxide compound selectively reacts with an aluminum oxide surface to form cerium oxide on an aluminum oxide surface after calcination. This deposition / calcination step can be repeated until a layer of desired thickness is reached. Suitable aluminum-containing precursors are, for example, aluminum oxide, such as gibbsite, boehmite γ aluminum oxide, δ aluminum oxide or θ aluminum oxide or a combination thereof. The mixture thus obtained can then be converted to a cerium-alumina composite material by the calcination step of the mixture.
[0064] Ceria-Zirconia Mixed Oxide (CZO) :
[0065] The term composite metal oxide refers to a mixed metal oxide containing oxygen anions and at least two different metal cations. In ceria-zirconia mixed oxides, cerium cations and zirconium cations are distributed within the oxide lattice structure. The terms "composite oxide" and "mixed oxide" are used interchangeably. Since the metal cations are distributed within the oxide lattice structure, these structures are also often referred to as solid solutions.
[0066] Preferably, the amount of ceria-zirconia mixed oxide present in the first catalytic layer and the second catalytic layer is 20 wt % to 80 wt % based on the total weight of the first catalytic layer and the second catalytic layer. More preferably, the amount of ceria-zirconia mixed oxide present in the first catalytic layer and the second catalytic layer is in the range of 30 wt % to 70 wt % based on the total weight of the first catalytic layer and the second catalytic layer. Most preferably, the amount of ceria-zirconia mixed oxide present in the first catalytic layer and the second catalytic layer is in the range of 40 wt % to 60 wt % based on the total weight of the first catalytic layer and the second catalytic layer.
[0067] Preferably, the ceria (as CeO 2 ) present in the ceria-zirconia mixed oxide in the first or second layer is 10%, based on the total weight of the ceria-zirconia mixed oxide present in the corresponding layer. 2 % (calculated as ZrO ) is present in an amount of 10% to 60% by weight, and the zirconium oxide (calculated as ZrO ) present in the first layer or the second layer is present in an amount of 10% to 60% by weight, based on the total weight of the ceria-zirconia mixed oxide present in the corresponding layer. 2 % to 90% by weight).
[0068] More preferably, the ceria (as CeO 2 ) present in the ceria-zirconia mixed oxide in the first layer or the second layer is 1 wt % based on the total weight of the ceria-zirconia mixed oxide in the corresponding catalytic layer. 2 % (calculated as ZrO) is present in an amount of 20 wt. % to 50 wt. %, and the zirconium oxide (calculated as ZrO) of the ceria-zirconia mixed oxide present in the first layer or the second layer is present in an amount of 20 wt. % to 50 wt. %, based on the total weight of the ceria-zirconia mixed oxide in the corresponding catalytic layer. 2 % to 80% by weight).
[0069] Even more preferably, the ceria (as CeO 2 ) present in the ceria-zirconia mixed oxide in the first layer or in the second layer is 1 wt % based on the total weight of the ceria-zirconia mixed oxide in the corresponding catalytic layer. 2 % (calculated as ZrO) is present in an amount of 30 wt. % to 50 wt. %, and the zirconium oxide (calculated as ZrO) present in the ceria-zirconia mixed oxide of the first layer or the second layer is present in an amount of 30 wt. % to 50 wt. %, based on the total weight of the ceria-zirconia mixed oxide in the corresponding catalytic layer. 2 % to 70% by weight).
[0070] The ceria-zirconia mixed oxide is used as an oxygen storage component. The term "oxygen storage component" (OSC) refers to an entity having a multivalent state and capable of actively reacting with a reducing agent such as carbon monoxide (CO) and / or hydrogen under reducing conditions, and then reacting with an oxidizing agent such as oxygen or nitrogen oxides under oxidizing conditions.
[0071] In a preferred embodiment, the ceria-zirconia mixed oxide present in the first layer or the second layer contains a dopant selected from lanthanum oxide, titanium dioxide, hafnium dioxide, magnesium oxide, calcium oxide, strontium oxide, barium oxide, yttrium, hafnium, praseodymium, neodymium or any combination thereof. The dopant metal may be incorporated into the crystal structure of the composite metal oxide in cationic form, may be deposited on the surface of the composite metal oxide in oxidized form, or may be present in oxidized form as a blend of a mixture of both the dopant and the composite metal oxide on a microscopic scale, that is to say in the form of a composite material with the composite metal oxide. Preferably, the dopant is contained in an amount of 1.0% to 20% by weight, or more preferably in an amount of 5.0% to 15% by weight, based on the total weight of the ceria-zirconia mixed oxide present in the corresponding layer.
[0072] Alumina :
[0073] The alumina present in the first catalytic layer and the second catalytic layer is preferably gamma alumina or activated alumina. Its BET surface area for fresh material is usually in excess of 60 square meters per gram ("m2 / g"), and is usually up to about 200 m2 / g. 2 / g or more. Activated alumina is usually a mixture of γ and δ phases of alumina, but may also contain a large amount of η, κ and θ alumina phases. Preferably, the activated alumina is a high bulk density γ-alumina, a low or medium bulk density macroporous γ-alumina, a low bulk density macroporous boehmite or a γ-alumina.
[0074] Preferably, the amount of aluminum oxide present in the first catalytic layer and the second catalytic layer is in the range of 1.0 wt% to 40 wt% based on the total weight of the first catalytic layer and the second catalytic layer. More preferably, the amount of aluminum oxide present in the first catalytic layer and the second catalytic layer is in the range of 5.0 wt% to 30 wt% based on the total weight of the first catalytic layer and the second catalytic layer. Most preferably, the amount of aluminum oxide present in the first catalytic layer and the second catalytic layer is in the range of 5.0 wt% to 20 wt% based on the total weight of the first catalytic layer and the second catalytic layer.
[0075] The aluminum oxide present in the first catalytic layer and the second catalytic layer is preferably doped with a dopant selected from barium, lanthanum oxide, zirconium oxide, neodymium oxide, yttrium oxide, ceria or titania, wherein the amount of the dopant is preferably 1.0 wt% to 30 wt% based on the total weight of the aluminum oxide and the dopant present in the first catalytic layer and the second catalytic layer. More preferably, the aluminum oxide doped with a dopant is selected from lanthanum oxide-aluminum oxide, titania-aluminum oxide, ceria-zirconia-aluminum oxide, zirconium oxide-aluminum oxide, lanthanum oxide-zirconia-aluminum oxide, barium oxide-aluminum oxide, barium oxide-lanthanum oxide-aluminum oxide, barium oxide-lanthanum oxide-neodymium oxide-aluminum oxide or any combination thereof.
[0076] Substrate :
[0077] The substrate of the catalytic article of the presently claimed invention may be composed of any material commonly used to prepare automotive catalysts. In preferred embodiments, the substrate is a ceramic substrate, a metal substrate, a ceramic foam substrate, a polymer foam substrate, or a woven fiber substrate. In more preferred embodiments, the substrate is a ceramic or metal monolithic honeycomb structure.
[0078] The substrate provides a plurality of wall surfaces onto which the catalytic layer or washcoat described herein above is applied and adhered, thereby serving as a support for the catalytic material.
[0079] Preferred metal substrates include heat-resistant metals and metal alloys, such as titanium and stainless steel, and other alloys in which iron is a substantial or major component. Such alloys may contain one or more of nickel, chromium and / or aluminum, and the total amount of these metals may advantageously constitute at least 15% by weight of the alloy, such as 10% to 25% by weight of chromium, 3% to 8% of aluminum, and up to 20% by weight of nickel. The alloy may also contain small or trace amounts of one or more metals, such as manganese, copper, vanadium, titanium, etc. The surface of the metal substrate may be oxidized at high temperatures (e.g., 1000° C. and higher) to form an oxide layer on the surface of the substrate, thereby improving the corrosion resistance of the alloy and promoting adhesion of the carrier coating to the metal surface.
[0080] Preferred ceramic materials for constructing the substrate may include any suitable refractory material, for example, cordierite, mullite, cordierite-alumina, silicon nitride, zircon-mullite, spodumene, alumina-silica magnesia, zirconium silicate, sillimanite, magnesium silicate, zircon, petalite, alumina, aluminosilicates, and the like.
[0081] Any suitable substrate can be used, such as a monolithic flow-through substrate having a plurality of fine parallel gas flow channels extending from the inlet face of the substrate to the outlet face so that the channel is open to allow fluid to flow. The channel, which is essentially a straight path from the inlet to the outlet, is defined by a wall, and the walls are coated with a catalytic material as a carrier coating so that the gas flowing through the channel contacts the catalytic material. The flow channels of the monolithic substrate are thin-walled channels, which are in any suitable cross-sectional shape, such as trapezoidal, rectangular, square, sinusoidal, hexagonal, elliptical, circular, etc. Such structures contain about 60 to about 1200 or more gas inlet openings (i.e., "cells") per square inch of cross section (cpsi), more typically about 300 cpsi to 900 cpsi. The wall thickness of the flow-through substrate can vary, with a typical range of between 0.002 inches and 0.1 inches. A representative commercially available flow-through substrate is a cordierite substrate with 400 cpsi and 6 mil wall thickness or 600 cpsi and 4 mil wall thickness. However, it should be understood that the present invention is not limited to a specific substrate type, material or geometry. In an alternative embodiment, the substrate can be a wall-flow substrate, wherein each channel is blocked with a non-porous plug at one end of the substrate body, wherein the alternating channels are blocked at the opposite end faces. This requires gas flow through the porous wall of the wall-flow substrate to reach the outlet. Such a monolithic substrate can contain up to about 700 or higher cpsi, such as about 100 cpsi to 400 cpsi, and more typically about 200 cpsi to about 300 cpsi. The cross-sectional shape of the unit cell can be varied as described above. The wall thickness of the wall-flow substrate is generally between 0.002 inches and 0.1 inches. A representative commercially available wall-flow substrate is composed of porous cordierite, an example of which has 200 cpsi and a wall thickness of 10 mils, or has 300 cpsi and a wall thickness of 8 mils, and a wall porosity of 45%-65%. Other ceramic materials (such as aluminum titanate, silicon carbide and silicon nitride) are also used as wall flow filter substrates. However, it should be understood that the present invention is not limited to a specific substrate type, material or geometry. It should be noted that in the case where the substrate is a wall flow substrate, the catalyst composition can penetrate into the pore structure of the porous wall (i.e., partially or completely block the pore openings) in addition to being disposed on the surface of the wall. In one embodiment, the substrate has a flow-through ceramic honeycomb structure, a wall flow ceramic honeycomb structure or a metal honeycomb structure.
[0082] Figure 4A and Figure 4B An exemplary substrate 2 is shown in the form of a flow-through substrate coated with a washcoat composition / catalytic layer as described herein. Figure 4A, the exemplary substrate 2 has a cylindrical shape and a cylindrical outer surface 4, an upstream end face 6, and a corresponding downstream end face 8 that is identical to the end face 6. The substrate 2 has a plurality of fine parallel gas flow channels 10 formed therein. Figure 4B As seen in FIG. 1 , the flow channel 10 is formed by the wall 12 and extends through the substrate 2 from the upstream end face 6 to the downstream end face 8, and the channel 10 is unobstructed to allow a fluid (e.g., a gas stream) to flow longitudinally through the substrate 2 via its gas flow channel 10. As shown in FIG. Figure 4B As can be more easily seen in the , the size and configuration of the wall 12 are such that the gas flow channel 10 has a substantially regular polygonal shape. As shown, if desired, the washcoat composition / catalytic layer can be applied in multiple, distinct layers. In the illustrated embodiment, the washcoat is comprised of a discrete first washcoat layer 14 adhered to the wall 12 of the substrate member and a second discrete second washcoat layer 16 coated on top of the first washcoat layer 14. In one embodiment, the presently claimed invention is also practiced with two or more (e.g., 3 or 4) washcoat layers and is not limited to the illustrated two-layer embodiment.
[0083] Figure 5 An exemplary substrate 2 is shown in the form of a wall flow filter substrate coated with a washcoat composition as described herein. Figure 5 As seen in the example substrate 2, there are a plurality of channels 52. These channels are tubularly surrounded by the inner wall 53 of the filter substrate. The substrate has an inlet end 54 and an outlet end 56. Alternating channels are plugged at the inlet end with an inlet plug 58 and at the outlet end with an outlet plug 60 to form a relative checkerboard pattern at the inlet 54 and outlet 56. The gas flow 62 enters through the unblocked channel inlet 64, is blocked by the outlet plug 60, and diffuses through the channel wall 53 (which is porous) to the outlet side 66. The gas cannot return to the inlet side of the wall due to the inlet plug 58. The porous wall flow filter used in the present invention is catalyzed because the wall of the element has or contains one or more catalytic materials. The catalytic material may be present alone on the inlet side of the element wall, alone on the outlet side, on both the inlet side and the outlet side, or the wall itself may be composed of the catalytic material in whole or in part. The present invention includes the use of one or more layers of catalytic material on the inlet and / or outlet wall of the element.
[0084] Carrier coating on substrate :
[0085] The substrate is coated with catalytic layers, namely a first catalytic layer and a second catalytic layer in a zoned manner. The first zone is coated with the first catalytic layer, and the second zone is coated with the second catalytic layer. The first catalytic layer covers 60% to 100% of the area of the first zone, and the second catalytic layer covers 60% to 100% of the area of the second zone.
[0086] The first region occupies an inflow end portion of the substrate, and the second region occupies an outflow end portion of the substrate.
[0087] The first and second zones together cover 50% to 100% of the length of the substrate. Preferably, the first and second zones together cover 90% to 100% of the length of the substrate, and more preferably, the first and second zones together cover the entire length or the entire accessible surface area of the substrate.
[0088] The term "accessible surface" refers to the surface of the substrate that can be coated using conventional coating techniques used in the art of catalyst preparation, such as impregnation techniques.
[0089] Preferably, the first zone covers 10% to 90% of the total length of the substrate from the inlet, and the second zone covers 90% to 10% of the total length of the substrate from the outlet, while the first zone and the second zone together cover 20% to 100% of the length of the substrate. More preferably, the first zone covers 20% to 80% of the total length of the substrate from the inlet, and the second zone covers 80% to 20% of the total length of the substrate from the outlet, while the first zone and the second zone together cover 40% to 100% of the length of the substrate. Even more preferably, the first zone covers 30% to 70% of the total length of the substrate from the inlet, and the second zone covers 70% to 30% of the total length of the substrate from the outlet, while the first zone and the second zone together cover 60% to 100% of the length of the substrate. Even most preferably, the first zone covers 40% to 50% of the total length of the substrate from the inlet, and the second zone covers 50% to 40% of the total length of the substrate from the outlet, while the first zone and the second zone together cover 80% to 100% of the length of the substrate.
[0090] District 1 :
[0091] The first zone is coated with a first catalytic layer comprising platinum supported on a ceria-zirconia mixed oxide or a ceria-alumina composite material or both; and rhodium supported on a ceria-zirconia mixed oxide or a ceria-alumina composite material or both.
[0092] Preferably, the first catalytic layer covers 60% to 100% of the area of the first zone. More preferably, the first catalytic layer covers 70% to 100% of the area of the first zone. Most preferably, the first catalytic layer covers 80% to 100% of the area of the first zone.
[0093] Preferably, the amount of platinum in the first catalytic layer is 0.02 wt % to 3.0 wt % based on the total weight of the first catalytic layer. More preferably, the amount of platinum in the first catalytic layer is 0.02 wt % to 2.5 wt % based on the total weight of the first catalytic layer. Even more preferably, the amount of platinum in the first catalytic layer is 0.05 wt % to 2.0 wt % based on the total weight of the first catalytic layer.
[0094] Based on the total weight of platinum in the first catalytic layer and the second catalytic layer, the amount of platinum loaded on the ceria-zirconia mixed oxide or the ceria-alumina composite material or both in the first catalytic layer is preferably 60 wt % to 100 wt %. More preferably, based on the total weight of platinum in the first catalytic layer and the second catalytic layer, the amount of platinum loaded on the ceria-zirconia mixed oxide or the ceria-alumina composite material or both in the first catalytic layer is 70 wt % to 100 wt %. Most preferably, based on the total weight of platinum in the first catalytic layer and the second catalytic layer, the amount of platinum loaded on the ceria-zirconia mixed oxide or the ceria-alumina composite material or both in the first catalytic layer is 80 wt % to 100 wt %.
[0095] The first catalytic layer also includes rhodium supported on ceria-zirconia mixed oxide or ceria-alumina composite material or both. Preferably, based on the gross weight of the first catalytic layer, the total amount of rhodium in the first catalytic layer is 0.01 wt % to 1.0 wt %. More preferably, based on the gross weight of the first catalytic layer, the total amount of rhodium in the first catalytic layer is 0.01 wt % to 0.5 wt %.
[0096] Preferably, the amount of rhodium supported on the ceria-zirconia mixed oxide or the ceria-alumina composite material or both in the first catalytic layer is 50 wt % to 100 wt % based on the total weight of rhodium in the first catalytic layer and the second catalytic layer. More preferably, the amount of rhodium supported on the ceria-zirconia mixed oxide or the ceria-alumina composite material or both in the first catalytic layer is 75 wt % to 100 wt % based on the total weight of rhodium in the first catalytic layer and the second catalytic layer.
[0097] In addition, the first catalytic layer preferably comprises palladium. Preferably, palladium is supported on ceria-zirconia mixed oxide or ceria-alumina composite material or both. More preferably, palladium is supported on ceria-zirconia mixed oxide. Preferably, the amount of palladium in the first layer is 0 wt % to 50 wt % based on the total weight of palladium present in the first layer and the second layer. More preferably, the amount of palladium in the first layer is 0.1 wt % to 30 wt % based on the total weight of palladium present in the first layer and the second layer.
[0098] Even more preferably, the amount of palladium in the first layer is from 0.1 wt. % to 25 wt. %, based on the total weight of palladium present in the first layer and the second layer.
[0099] The amount of ceria-zirconia mixed oxide in the first catalytic layer is preferably in the range of 20 wt % to 80 wt % based on the total weight of the first catalytic layer. More preferably, the amount of ceria-zirconia mixed oxide in the first catalytic layer is in the range of 25 wt % to 70 wt % based on the total weight of the first catalytic layer. Most preferably, the amount of ceria-zirconia mixed oxide in the first catalytic layer is in the range of 30 wt % to 60 wt % based on the total weight of the first catalytic layer.
[0100] The ceria-zirconia mixed oxide preferably comprises: CeO in an amount of about 10 to 60 wt %, based on the total weight of the ceria-zirconia mixed oxide present in the first catalytic layer. 2 and based on the total weight of the ceria-zirconia mixed oxide present in the first catalytic layer, from about 40% by weight to about 90% by weight of ZrO 2 More preferably, the ceria-zirconia mixed oxide comprises: CeO in an amount of about 20 wt % to 50 wt % based on the total weight of the ceria-zirconia mixed oxide present in the first catalytic layer. 2 and based on the total weight of the ceria-zirconia mixed oxide present in the first catalytic layer, from about 50% by weight to about 80% by weight of ZrO 2 Even more preferably, the ceria (as CeO 2 ) present in the ceria-zirconia mixed oxide in the first catalytic layer is 0.1 wt % tantalum (0.1 wt % tantalum) based on the total weight of the ceria-zirconia mixed oxide in the first catalytic layer. 2 % (calculated as ZrO) is present in an amount of 30 wt % to 50 wt %, and the zirconium oxide (calculated as ZrO) present in the first layer is present in an amount of 30 wt % to 50 wt %, based on the total weight of the ceria-zirconia mixed oxide in the first layer. 2 % to 70% by weight).
[0101] Preferably, the amount of the ceria-alumina composite material in the first catalytic layer is in the range of 10 wt % to 80 wt % based on the total weight of the first catalytic layer. More preferably, the amount of the ceria-alumina composite material in the first catalytic layer is in the range of 20 wt % to 70 wt % based on the total weight of the first catalytic layer. More preferably, the amount of the ceria-alumina composite material in the first catalytic layer is in the range of 30 wt % to 60 wt % based on the total weight of the first catalytic layer.
[0102] Preferably, the weight of the ceria-alumina composite material present in the first catalytic layer is CeO 2The calculated amount of ceria is 1.0 wt % to 60 wt %. More preferably, the amount of ceria-alumina composite material present in the first layer ...%, based on the total weight of the ceria-alumina composite material present in the first catalytic layer. 2 The calculated amount of ceria is 5.0 wt % to 50 wt %. More preferably, the amount of ceria-alumina composite material present in the first layer ...%, based on the total weight of the ceria-alumina composite material present in the first catalytic layer. 2 The calculated amount of ceria is 5.0 wt % to 30 wt %. Even more preferably, the amount of ceria-alumina composite material present in the first layer in the form of CeO is 5.0 wt % to 30 wt %, based on the total weight of the ceria-alumina composite material present in the first catalytic layer. 2 The calculated amount of cerium dioxide is 8.0 wt% to 20 wt%.
[0103] District 2 :
[0104] The second zone is coated with a second catalytic layer comprising palladium supported on a ceria-zirconia mixed oxide, alumina, a ceria-alumina composite material, or any combination thereof; and rhodium supported on a ceria-zirconia mixed oxide, alumina, a ceria-alumina composite material, or any combination thereof. Preferably, the second catalytic layer covers 60% to 100% of the area of the second zone. More preferably, the second catalytic layer covers 70% to 100% of the area of the second zone. Most preferably, the second catalytic layer covers 80% to 100% of the area of the second zone.
[0105] Preferably, based on the gross weight of the second catalytic layer, the amount of palladium is in the range of 0.02 wt % to 5.0 wt %. More preferably, based on the gross weight of the second catalytic layer, the amount of palladium is in the range of 0.02 wt % to 4.0 wt %. Based on the gross weight of palladium in the first catalytic layer and the second catalytic layer, the amount of palladium loaded on ceria-zirconia mixed oxide, aluminum oxide, ceria-alumina composite material or any combination thereof in the second catalytic layer is preferably 50 wt % to 100 wt %. More preferably, based on the gross weight of palladium in the first catalytic layer and the second catalytic layer, the amount of palladium loaded on ceria-zirconia mixed oxide, aluminum oxide, ceria-alumina composite material or any combination thereof in the second catalytic layer is 60 wt % to 100 wt %. Most preferably, based on the gross weight of palladium in the first catalytic layer and the second catalytic layer, the amount of palladium loaded on ceria-zirconia mixed oxide, aluminum oxide, ceria-alumina composite material or any combination thereof in the second catalytic layer is 75 wt % to 100 wt %.
[0106] The second catalytic layer preferably comprises rhodium supported on ceria-zirconia mixed oxide, alumina, ceria-alumina composites or any combination thereof.
[0107] Preferably, the amount of rhodium is in the range of 0.01 wt% to 1.0 wt% based on the total weight of the second catalytic layer. More preferably, the amount of rhodium is in the range of 0.03 wt% to 0.5 wt% based on the total weight of the second catalytic layer.
[0108] Preferably, the amount of rhodium supported on ceria-zirconia mixed oxide, alumina, ceria-alumina composite material or any combination thereof in the second catalytic layer is preferably 0 wt % to 50 wt % based on the total weight of rhodium in the first catalytic layer and the second catalytic layer. More preferably, the amount of rhodium supported on ceria-zirconia mixed oxide, alumina, ceria-alumina composite material or any combination thereof in the second catalytic layer is 0 wt % to 25 wt % based on the total weight of rhodium in the first catalytic layer and the second catalytic layer.
[0109] The second catalytic layer optionally comprises platinum supported on ceria-zirconia mixed oxide, alumina, ceria-alumina composite material or any combination thereof. Preferably, the amount of platinum supported on ceria-zirconia mixed oxide, alumina, ceria-alumina composite material or any combination thereof is 0 wt % to 50 wt % based on the total weight of the platinum present in the first and second layers. More preferably, the amount of platinum supported on ceria-zirconia mixed oxide, alumina, ceria-alumina composite material or any combination thereof is 0.1 wt % to 30 wt % based on the total weight of the platinum present in the first and second layers. Even more preferably, the amount of platinum supported on ceria-zirconia mixed oxide, alumina, ceria-alumina composite material or any combination thereof is 0.1 wt % to 25 wt % based on the total weight of the platinum present in the first and second layers.
[0110] The amount of ceria-zirconia mixed oxide in the second catalytic layer is in the range of 20 wt % to 80 wt % based on the total weight of the second catalytic layer. Preferably, the amount of ceria-zirconia mixed oxide in the second catalytic layer is in the range of 25 wt % to 70 wt % based on the total weight of the second catalytic layer. More preferably, the amount of ceria-zirconia mixed oxide in the second catalytic layer is in the range of 30 wt % to 60 wt % based on the total weight of the second catalytic layer.
[0111] The ceria-zirconia mixed oxide preferably comprises: CeO in an amount of about 10 to 60 wt %, based on the total weight of the ceria-zirconia mixed oxide present in the second catalytic layer. 2and based on the total weight of the ceria-zirconia mixed oxide present in the second catalytic layer, about 40 wt % to about 90 wt % of ZrO 2 More preferably, the ceria-zirconia mixed oxide comprises: CeO in an amount of about 20 wt % to 50 wt % based on the total weight of the ceria-zirconia mixed oxide present in the second catalytic layer. 2 and based on the total weight of the ceria-zirconia mixed oxide present in the second catalytic layer, about 50 wt % to about 80 wt % of ZrO 2 Even more preferably, the ceria (as CeO ) present in the ceria-zirconia mixed oxide in the second catalytic layer is 0.1 wt % tantalum (0.1 wt % tantalum) based on the total weight of the ceria-zirconia mixed oxide in the second catalytic layer. 2 % (calculated as ZrO) is present in an amount of 30 to 50 wt. %, and the zirconium oxide (calculated as ZrO) of the ceria-zirconia mixed oxide present in the layer is present in an amount of 30 to 50 wt. %, based on the total weight of the ceria-zirconia mixed oxide in the second catalytic layer. 2 % to 70% by weight).
[0112] Based on the total weight of the second catalytic layer, the amount of alumina in the second catalytic layer is preferably in the range of 5.0 wt % to 50 wt %. More preferably, based on the total weight of the second catalytic layer, the amount of alumina in the second catalytic layer is in the range of 10 wt % to 40 wt %.
[0113] Preferably, the amount of the ceria-alumina composite material in the second catalytic layer is in the range of 1.0 wt % to 40 wt % based on the total weight of the second catalytic layer. More preferably, the amount of the ceria-alumina composite material in the second catalytic layer is in the range of 1.0 wt % to 30 wt % based on the total weight of the first catalytic layer. More preferably, the amount of the ceria-alumina composite material in the second catalytic layer is in the range of 1.0 wt % to 20 wt % based on the total weight of the second catalytic layer.
[0114] Preferably, the amount of CeO in the ceria-alumina composite material present in the second catalytic layer is 100%, based on the total weight of the ceria-alumina composite material present in the second catalytic layer. 2 The calculated amount of ceria is 1.0 wt % to 60 wt %. More preferably, the amount of ceria-alumina composite material present in the second catalytic layer is 1.0 wt % to 60 wt %. More preferably, the amount of ceria-alumina composite material present in the second catalytic layer is 1.0 wt % to 60 wt %. 2The calculated amount of ceria is 5.0 wt % to 50 wt %. More preferably, the amount of ceria-alumina composite material present in the second catalytic layer ... 2 The calculated amount of ceria is 5.0 wt % to 30 wt %. Even more preferably, the amount of ceria-alumina composite material present in the second catalytic layer is 5.0 wt % to 30 wt %. Even more preferably, the amount of ceria-alumina composite material present in the second catalytic layer is 5.0 wt % to 30 wt %. 2 The calculated amount of cerium dioxide is 8.0 wt% to 20 wt%.
[0115] Preferably, the weight ratio of rhodium loaded on cerium dioxide-zirconia mixed oxide or cerium dioxide-alumina composite material or both in the first catalytic layer to rhodium loaded on cerium dioxide-zirconia mixed oxide, alumina, cerium dioxide-alumina composite material or any combination thereof in the second catalytic layer is in the range of 1.5:1 to 4:1.
[0116] External coating :
[0117] The first zone also includes an outer coating layer deposited on at least a portion of the first zone. The outer coating layer comprises a porous refractory oxide and optionally at least one base metal oxide.
[0118] As used herein, "porous refractory oxide" refers to porous metal oxide-containing materials that exhibit chemical and physical stability at high temperatures. Exemplary refractory oxides include alumina, silica, zirconia, titania, ceria, and physical mixtures or chemical combinations thereof, including atomically doped combinations and including high surface area or active compounds such as activated alumina.
[0119] Preferably, the porous refractory oxide is stabilized alumina or unstabilized alumina.
[0120] Preferably, the loading of the topcoat divided by the volume of the substrate coated by the topcoat is less than 1 gram per cubic inch.
[0121] Preferably, the outer coating is substantially free of precious metals and optionally comprises an oxygen storage component. The term "substantially free of precious metals" means that no precious metal is added to the outer coating. It may be present as an impurity in an amount of less than 0.001% by weight. Preferably, the base metal oxide is an alkaline earth metal oxide or a rare earth metal oxide. The alkaline earth metal oxide is preferably selected from barium oxide, magnesium oxide, calcium oxide, strontium oxide or a combination thereof. More preferably, the alkaline earth metal oxide is selected from barium oxide and strontium oxide. Most preferably, the alkaline earth metal oxide is barium oxide.
[0122] Preferably, the rare earth metal oxide is at least one oxide of a rare earth metal selected from Ce, Pr, Nd, Eu, Sm, Yb and La, or a mixture thereof. More preferably, the rare earth metal oxide is at least one oxide of a rare earth metal selected from Ce, Pr and La, or a mixture thereof.
[0123] Preferably, the length of the outer coating is equal to or less than 50% of the total length of the substrate. More preferably, the length of the outer coating is equal to or less than 35% of the total length of the substrate. Most preferably, the length of the outer coating is equal to or less than 32% of the total length of the substrate.
[0124] Preparation of catalytic products :
[0125] In another aspect of the present invention, there is also provided a method for preparing the catalytic product described herein above. The method comprises the following steps:
[0126] -Preparing a first catalytic layer slurry comprising platinum supported on ceria-zirconia mixed oxide or ceria-alumina composite or both; and rhodium supported on ceria-zirconia mixed oxide, ceria-alumina composite, alumina or any combination thereof.
[0127] -Prepare a second catalytic layer slurry comprising palladium supported on ceria-zirconia mixed oxide, alumina, ceria-alumina composite material or any combination thereof; and rhodium supported on ceria-zirconia mixed oxide, alumina, ceria-alumina composite material or any combination thereof.
[0128] - Coating the first catalytic layer slurry on the inflow end portion of the substrate to obtain a first zone.
[0129] - Coating a second catalytic layer slurry on the outflow end portion of the substrate to obtain a second zone.
[0130] - The substrate is then subjected to calcination at a temperature ranging from 400°C to 700°C.
[0131] The step of preparing the slurry comprises a technique selected from the group consisting of incipient wetness impregnation, incipient wetness co-impregnation and post addition.
[0132] The incipient wetness impregnation technique, also known as capillary impregnation or dry impregnation, is commonly used to synthesize heterogeneous materials, i.e., catalysts. Typically, a metal precursor is dissolved in an aqueous or organic solution, and the metal-containing solution is then added to a catalyst support that contains a pore volume equal to the volume of solution added. Capillary action draws the solution into the pores of the support. The volume of the added solution exceeding the pores of the support causes the transport of the solution to shift from a capillary action process to a much slower diffusion process. The catalyst is dried and calcined to remove the volatile components in the solution, depositing the metal on the surface of the catalyst support. The concentration profile of the impregnated material depends on the mass transfer conditions in the pores during impregnation and drying.
[0133] The support particles are usually dried sufficiently to absorb substantially all of the solution to form a wet solid. Typically, aqueous solutions of water-soluble compounds or complexes of the active metals are used, such as rhodium chloride, rhodium nitrate (e.g., Rh(NO) 3 and its salts), rhodium acetate, or a combination thereof (where rhodium is the active metal); palladium nitrate, palladium tetraamine nitrate, palladium acetate, or a combination thereof (where palladium is the active metal); and platinum nitrate, platinum acetate, or a combination thereof (where platinum is the active metal). After treating the support particles with the active metal solution, the particles are dried, such as by heat treating the particles at an elevated temperature (e.g., 100° C.-150° C.) for a period of time (e.g., 1 hour-3 hours), and then calcined to convert the active metal to a more catalytically active form. An exemplary calcination method involves heat treatment in air at a temperature of about 400° C.-550° C. for 10 minutes to 3 hours. The above method can be repeated as needed to achieve the desired active metal impregnation level.
[0134] Substrate coating :
[0135] The catalyst composition as described above is usually prepared in the form of catalyst particles as described above. These catalyst particles are mixed with water to form a slurry to coat catalyst substrates such as honeycomb substrates. In addition to the catalyst particles, the slurry may optionally contain a binder, an associative thickener and / or a surfactant (including anionic, cationic, nonionic or amphoteric surfactants) in the form of aluminum oxide, silicon dioxide, zirconium acetate, colloidal zirconium oxide or zirconium hydroxide. Other exemplary binders include boehmite, γ-alumina or δ / θ alumina and silica sol. When present, the binder is usually used in an amount of about 1.0 wt %-5.0 wt % of the total carrier coating loading. Acidic or alkaline substances are added to the slurry to adjust the pH accordingly. For example, in some embodiments, the pH of the slurry is adjusted by adding ammonium hydroxide, aqueous nitric acid solution or acetic acid. The typical pH range of the slurry is about 3.0 to 12. The slurry can be ground to reduce the particle size and enhance particle mixing. Grinding is done in a ball mill, continuous mill or other similar equipment, and the solid content of the slurry can be, for example, about 20% to 60% by weight, more specifically about 20% to 40% by weight. In one embodiment, the slurry after grinding is characterized by D 90 The particle size is about 10 microns to about 40 microns, preferably 10 microns to about 30 microns, more preferably about 10 microns to about 15 microns. Use a dedicated particle size analyzer to determine D 90 The equipment used in this example uses laser diffraction to measure particle size in small volumes of slurry. Typically, D 90 In micrometers it is meant that 90% of the particles by number have a diameter smaller than this value.
[0136] The slurry is coated on the catalyst substrate using any washcoat technique known in the art. For example, the catalyst substrate is dip-coated in the slurry one or more times or otherwise coated with the slurry. Thereafter, the coated substrate is dried at an elevated temperature (e.g., 100° C.-150° C.) for a period of time (e.g., 10 minutes-3.0 hours), and then calcined by heating, for example, at 400° C.-700° C., typically for about 10 minutes to about 3 hours. After drying and calcining, the final washcoat coating is considered to be substantially free of solvent.
[0137] After calcination, the catalyst loading obtained by the washcoat technique described above can be determined by calculating the difference between the coated and uncoated weights of the substrate. As will be apparent to one skilled in the art, the catalyst loading can be modified by altering the slurry rheology. In addition, the coating / drying / calcining process to produce the washcoat can be repeated as needed to build up the coating to the desired loading level or thickness, meaning that more than one washcoat may be applied.
[0138] The coated substrate can be aged by subjecting the coated substrate to a heat treatment. For example, aging is performed at a temperature of about 850° C. to about 1050° C. in the presence of steam under gasoline engine exhaust conditions for 50 hours to 300 hours. Thus, an aged catalyst article is provided according to the present invention. Effective support materials (such as ceria-alumina composites) maintain a high percentage (e.g., about 50%-100%) of their pore volume when aged (e.g., aged at about 850° C. to about 1050° C. in the presence of steam for about 50 hours to 300 hours).
[0139] Emission treatment system :
[0140] In another aspect of the present invention, an exhaust treatment system for an internal combustion engine is also provided, the system comprising the catalytic product described above. In an illustration, the system comprises a catalytic product according to the invention claimed herein and an additional three-way conversion (TWC) catalytic product based on platinum group metals. The catalytic product of the present invention can be placed in a close-coupled position. The tightly coupled catalyst is placed close to the engine so that they can reach the reaction temperature as quickly as possible. Typically, the tightly coupled catalyst is placed within three feet of the engine, more specifically, within one foot of the engine, and even more specifically, less than six inches from the engine. The tightly coupled catalyst is usually directly connected to the exhaust manifold. Since the tightly coupled catalyst is close to the engine, they are required to be stable at high temperatures. The catalytic product of the present invention can also be used as a part of an integrated exhaust system including one or more additional components for treating exhaust emissions. For example, the exhaust system, also referred to as an emission treatment system, can also include a tightly coupled TWC catalyst, an underfloor TWC catalyst, a catalytic soot filter (CSF) component and / or a selective catalytic reduction (SCR) catalytic product. The previous component list is merely illustrative and should not be considered to limit the scope of the present invention.
[0141] In another aspect of the invention, there is also provided a method for treating a gaseous exhaust stream comprising hydrocarbons, carbon monoxide and nitrogen oxides, the method comprising contacting the exhaust stream with a catalytic article according to the invention or an exhaust gas treatment system according to the invention. The invention also provides a method for reducing the levels of hydrocarbons, carbon monoxide and nitrogen oxides in a gaseous exhaust stream, the method comprising contacting the gaseous exhaust stream with a catalytic article according to the invention or an exhaust gas treatment system according to the invention to reduce the levels of hydrocarbons, carbon monoxide and nitrogen oxides in the exhaust gas.
[0142] In another aspect of the present invention, there is also provided the use of a catalytic article or an exhaust gas treatment system according to the presently claimed invention for purifying a gaseous exhaust stream comprising hydrocarbons, carbon monoxide and nitrogen oxides.
[0143] The invention is further illustrated by the following set of embodiments and combinations of embodiments resulting from the indicated dependencies and back-references. In particular, it should be noted that in each case where a scope of embodiments is mentioned, for example in the context of a term such as "a method according to any one of embodiments 1 to 4", each embodiment within the scope is meant to be explicitly disclosed to the skilled person, i.e. the wording of the term should be understood by the skilled person as being synonymous with "a method according to any one of embodiments 1, 2, 3 and 4". Furthermore, it is explicitly noted that the following set of embodiments is not a set of claims determining the degree of protection, but rather represents a properly structured part of the description of general and preferred aspects of the invention.
[0144] Implementation 1 :
[0145] The present invention provides a catalytic product, which comprises:
[0146] a) substrate;
[0147] b) a first zone coated with a first catalytic layer; and
[0148] c) a second zone, which is coated with a second catalytic layer,
[0149] wherein the first catalytic layer comprises platinum supported on a ceria-zirconia mixed oxide or a ceria-alumina composite material or both; and rhodium supported on a ceria-zirconia mixed oxide, a ceria-alumina composite material, alumina or any combination thereof,
[0150] wherein the second catalytic layer comprises palladium supported on ceria-zirconia mixed oxide, alumina, ceria-alumina composite material or any combination thereof; and rhodium supported on ceria-zirconia mixed oxide, alumina, ceria-alumina composite material or any combination thereof,
[0151] The first region occupies the inflow end portion of the substrate, and the second region occupies the outflow end portion of the substrate.
[0152] Implementation 2 :
[0153] A catalytic article according to embodiment 1, wherein the first catalytic layer further comprises palladium supported on a ceria-zirconia mixed oxide or a ceria-alumina composite material or both.
[0154] Implementation 3 :
[0155] A catalytic article according to any one of embodiments 1 to 2, wherein the second catalytic layer further comprises platinum supported on a ceria-zirconia mixed oxide, a ceria-alumina composite, alumina, or any combination thereof.
[0156] Implementation 4 :
[0157] A catalytic article according to any of Embodiments 1 to 3, wherein the total loading of the first catalytic layer and the second catalytic layer divided by the substrate volume is less than 3.2 grams per cubic inch.
[0158] Implementation 5 :
[0159] A catalytic article according to any one of embodiments 1 to 4, wherein the amount of platinum in the first catalytic layer and the second catalytic layer is in the range of 0.02 wt% to 3.0 wt% based on the total weight of the first catalytic layer and the second catalytic layer, wherein the amount of palladium in the first catalytic layer and the second catalytic layer is in the range of 0.02 wt% to 5.0 wt% based on the total weight of the first catalytic layer and the second catalytic layer, and wherein the amount of rhodium in the first catalytic layer and the second catalytic layer is in the range of 0.01 wt% to 1.0 wt% based on the total weight of the first catalytic layer and the second catalytic layer.
[0160] Implementation 6 :
[0161] A catalytic article according to any one of embodiments 1 to 5, wherein the total amount of platinum supported on ceria-zirconia mixed oxide or ceria-alumina composite material or both in the first catalytic layer is 80 wt% to 100 wt% based on the total weight of platinum in the first catalytic layer and the second catalytic layer, wherein the total amount of palladium supported on ceria-zirconia mixed oxide, alumina, ceria-alumina composite material or any combination thereof in the second catalytic layer is 75 wt% to 100 wt% based on the total weight of palladium in the first catalytic layer and the second catalytic layer, and wherein the weight ratio of rhodium supported on ceria-zirconia mixed oxide or ceria-alumina composite material or both in the first catalytic layer to rhodium supported on ceria-zirconia mixed oxide, alumina, ceria-alumina composite material or any combination thereof in the second catalytic layer is in the range of 1.5:1 to 4:1.
[0162] Implementation Plan 7 :
[0163] A catalytic article according to any one of embodiments 1 to 6, wherein the first zone further includes an outer coating deposited on at least a portion of the first zone, wherein the outer coating comprises a porous refractory oxide and optionally at least one base metal oxide.
[0164] Implementation 8 :
[0165] A catalytic article according to embodiment 7, wherein the outer coating is substantially free of precious metals and optionally comprises an oxygen storage component.
[0166] Implementation Plan 9 :
[0167] A catalytic article according to any one of embodiments 7 to 8, wherein the length of the outer coating is equal to or less than 50% of the total length of the substrate.
[0168] Implementation 10 :
[0169] A catalytic article according to any of embodiments 7 to 9, wherein the loading of the outer coating divided by the volume of the substrate coated by the outer coating is less than 1 gram per cubic inch.
[0170] Implementation Plan 11 :
[0171] A catalytic article according to any one of embodiments 7 to 10, wherein the porous refractory oxide is stabilized alumina or unstabilized alumina.
[0172] Implementation 12 :
[0173] A catalytic article according to any one of embodiments 7 to 11, wherein the base metal oxide is an alkaline earth metal oxide or a rare earth metal oxide, wherein the alkaline earth metal oxide is selected from barium oxide, magnesium oxide, calcium oxide, strontium oxide or a combination thereof, wherein the rare earth metal oxide is at least one oxide of a rare earth metal selected from Ce, Pr, Nd, Eu, Sm, Yb and La, or a mixture thereof.
[0174] Implementation 13 :
[0175] A catalytic product according to any one of embodiments 1 to 12, wherein the first zone covers 10% to 90% of the entire substrate length from the inlet end portion, wherein the second zone covers 10% to 90% of the entire substrate length from the outlet end portion, wherein the first catalytic layer covers 60% to 100% of the area of the first zone, and the second catalytic layer covers 60% to 100% of the area of the second zone.
[0176] Implementation Plan 14:
[0177] A catalytic article according to any one of embodiments 1 to 13, wherein the first zone covers 40% to 60% of the entire substrate length from the inflow end portion, and wherein the second zone covers 60% to 40% of the entire substrate length from the outflow end portion.
[0178] Implementation Plan 15 :
[0179] A catalytic article according to any one of embodiments 1 to 14, wherein the amount of the ceria-zirconia mixed oxide present in the first catalytic layer and the second catalytic layer is 40 wt% to 60 wt% based on the total weight of the first catalytic layer and the second catalytic layer.
[0180] Implementation Plan 16 :
[0181] A catalytic article according to any one of embodiments 1 to 15, wherein the amount of aluminum oxide present in the first catalytic layer and the second catalytic layer is in the range of 5 wt% to 20 wt% based on the total weight of the first catalytic layer and the second catalytic layer.
[0182] Implementation Plan 17 :
[0183] A catalytic article according to any one of embodiments 1 to 16, wherein the aluminum oxide is doped with a dopant selected from barium, lanthanum oxide, zirconium oxide, neodymium oxide, yttrium oxide, ceria or titanium oxide, wherein the amount of the dopant is 1.0 wt% to 30 wt% based on the total weight of the aluminum oxide and the dopant present in the first catalytic layer and the second catalytic layer.
[0184] Implementation Plan 18 :
[0185] A catalytic article according to any of embodiments 1 to 17, wherein the alumina is selected from alumina, lanthanum oxide-alumina, titania-alumina, ceria-zirconia-alumina, zirconia-alumina, ceria-alumina, lanthanum oxide-zirconia-alumina, barium oxide-alumina, barium oxide-lanthanum oxide-alumina, barium oxide-lanthanum oxide-neodymium oxide-alumina, or any combination thereof.
[0186] Implementation Plan 19 :
[0187] A catalytic article according to any one of embodiments 1 to 18, wherein the amount of the ceria-alumina composite material present in the first catalytic layer and the second catalytic layer is in the range of 15 wt% to 40 wt% based on the total weight of the first catalytic layer and the second catalytic layer.
[0188] Implementation Plan 20 :
[0189] The catalytic article according to any one of embodiments 1 to 19, wherein the cerium oxide-aluminum oxide composite material contains CeO 2 The calculated amount of cerium dioxide is 5.0 wt % to 30 wt %.
[0190] Implementation Plan 21 :
[0191] The catalytic article according to any one of embodiments 1 to 20, wherein the ceria-zirconia mixed oxide present in the first catalytic layer and the second catalytic layer comprises: CeO in an amount of 15 wt.% to 50 wt.%, based on the total weight of the ceria-zirconia mixed oxide in the corresponding catalytic layer. 2 Calculated ceria; and based on the total weight of the ceria-zirconia mixed oxide in the corresponding catalytic layer, 50 wt % to about 85 wt % of ZrO 2 Calculated zirconia.
[0192] Implementation Plan 22 :
[0193] A catalytic article according to any one of embodiments 1 to 21, wherein the ceria-zirconia mixed oxide present in the first catalytic layer and the second catalytic layer contains a dopant selected from lanthanum oxide, titanium dioxide, hafnium dioxide, magnesium oxide, calcium oxide, strontium oxide, barium oxide, yttrium, hafnium, praseodymium, neodymium or any combination thereof.
[0194] Implementation Plan 23 :
[0195] The catalytic article according to any one of embodiments 1 to 22, wherein the substrate is selected from a ceramic substrate, a metal substrate, a ceramic foam substrate, a polymer foam substrate, or a woven fiber substrate.
[0196] Implementation Plan 24 :
[0197] The present invention provides a method for preparing a catalytic article according to any one of embodiments 1 to 23, wherein the method comprises:
[0198] - preparing a first catalytic layer slurry comprising platinum supported on a ceria-zirconia mixed oxide or a ceria-alumina composite or both; and rhodium supported on a ceria-zirconia mixed oxide, a ceria-alumina composite, alumina or any combination thereof;
[0199] - preparing a second catalytic layer slurry comprising palladium supported on ceria-zirconia mixed oxide, alumina, ceria-alumina or any combination thereof; and rhodium supported on ceria-zirconia mixed oxide, alumina, ceria-alumina composite material or any combination thereof;
[0200] - coating the first catalytic layer slurry on the inflow end portion of the substrate to obtain a first zone;
[0201] - coating the second catalytic layer slurry on the outflow end portion of the substrate to obtain a second zone;
[0202] - subjecting the substrate to calcination at a temperature ranging from 400° C. to 700° C.,
[0203] The step of preparing the slurry comprises a technique selected from incipient wetness impregnation, incipient wetness co-impregnation and post addition.
[0204] Implementation Plan 25 :
[0205] The present invention provides an exhaust gas treatment system for an internal combustion engine, the system comprising the catalytic article according to any one of embodiments 1 to 23.
[0206] Implementation Plan 26 :
[0207] The present invention provides a method of treating a gaseous exhaust stream comprising hydrocarbons, carbon monoxide, and nitrogen oxides, the method comprising contacting the exhaust stream with a catalytic article according to any one of embodiments 1 to 23 or an exhaust treatment system according to embodiment 25.
[0208] Implementation Plan 27 :
[0209] The present invention provides a method for reducing the levels of hydrocarbons, carbon monoxide and nitrogen oxides in a gaseous exhaust stream, the method comprising contacting the gaseous exhaust stream with a catalytic product according to any one of embodiments 1 to 23 or an exhaust treatment system according to claim 25 to reduce the levels of hydrocarbons, carbon monoxide and nitrogen oxides in the exhaust gas.
[0210] Implementation Plan 28 :
[0211] The present invention provides the use of a catalytic article according to any one of embodiments 1 to 23 or an exhaust gas treatment system according to embodiment 25 for purifying a gaseous exhaust stream comprising hydrocarbons, carbon monoxide and nitrogen oxides.
[0212] Various aspects of the presently claimed invention are more fully illustrated by the following examples, which are set forth for the purpose of illustrating certain aspects of the invention and are not to be construed as limiting the invention.
[0213] Example 1: Comparative Catalytic Product A
[0214] Comparative catalytic product A is a PGM loading of 120 g / ft 3 A zoned dual-layer Pt / Pd / Rh catalytic article of (Pt / Pd / Rh=58 / 58 / 4) coated onto a cylindrical monolithic cordierite substrate having dimensions of 4.66" diameter and 3.81" length, a cell density of 800 cpsi and a wall thickness of 3 mils.
[0215] Ground floor entrance area : This zone covers 50% of the substrate length from the inlet to the middle, where the PGM loading is 104.4 g / ft 3 (Pt / Pd / Rh=0 / 104.4 / 0). A mixture containing about 25.4 wt% alumina, 62.5 wt% of a stabilized ceria-zirconia mixed oxide (OSC with about 40 wt% ceria), barium acetate yielding 7.8 wt% BaO, and ZrO yielding 2.0 wt% 2 A slurry of zirconium acetate and palladium nitrate yielding 2.36 wt% Pd was applied to the substrate. After calcination at 550°C for 1 hour in air, the washcoat loading of the inlet zone of the bottom layer was about 2.56 g / in 3 .
[0216] Exit area on the ground floor : This zone covers 50% of the substrate length from the outlet to the middle, where the PGM loading is 127.6 g / ft 3 (Pt / Pd / Rh=116 / 11.6 / 0). A cerium oxide-aluminum oxide composite material containing about 33.0 wt.% of about 8 wt.% of cerium oxide, 54.4 wt.% of a stabilized cerium oxide-zirconia mixed oxide (OSC with about 40 wt.% of cerium oxide), barium acetate to produce 7.8 wt.% of BaO, and AlO to produce 1.9 wt.% of AlO. 2 O 3 A slurry of a colloidal alumina binder of 1000 g / cm2, a platinum-amine complex yielding 2.61 wt% Pt, and palladium nitrate yielding 0.26 wt% Pd was applied to the substrate. After calcination at 550°C for 1 hour in air, the washcoat loading of the bottom layer in the outlet zone was about 2.57 g / in 3 .
[0217] Top floor : This layer covers 100% of the substrate length with a PGM loading of 4 g / ft 3(Pt / Pd / Rh=0 / 0 / 4). A slurry mixture containing about 84.8 wt% of a ceria-alumina composite material having about 8 wt% ceria, 15.0 wt% of a ceria-zirconia composite material having about 50 wt% ceria (binder), and rhodium nitrate to produce 0.23 wt% Rh was coated on the bottom layer. After calcination at 550°C for 1 hour in air, the washcoat loading of the top layer was about 1.00 g / in 3 .
[0218] Example 2: Comparative Catalytic Product B
[0219] Comparative catalytic product B is a PGM loading of 120 g / ft 3 A zoned dual-layer Pt / Pd / Rh catalytic article of (Pt / Pd / Rh=29 / 87 / 4) coated onto a cylindrical monolithic cordierite substrate having dimensions of 4.66" diameter and 3.81" length, a cell density of 800 cpsi and a wall thickness of 3 mils.
[0220] Ground floor entrance area : This zone covers 50% of the substrate length from the inlet to the middle, with a PGM loading of 156.6 g / ft 3 (Pt / Pd / Rh=0 / 156.6 / 0). A mixture containing about 25.1 wt% alumina, 61.8 wt% of a stabilized ceria-zirconia mixed oxide (OSC with about 40 wt% ceria), barium acetate yielding 7.7 wt% BaO, and ZrO yielding 1.9 wt% 2 A slurry of zirconium acetate and palladium nitrate yielding 3.50 wt% Pd was applied to the substrate. After calcination at 550°C for 1 hour in air, the washcoat loading of the inlet zone of the bottom layer was about 2.59 g / in 3 .
[0221] Exit area on the ground floor : This zone covers 50% of the substrate length from the outlet to the middle, with a PGM loading of 75.4 g / ft 3 (Pt / Pd / Rh=58 / 17.4 / 0). A composite material containing about 33.4 wt% of ceria-alumina with about 8 wt% ceria, 55.0 wt% of a stabilized ceria-zirconia mixed oxide (OSC with about 40 wt% ceria), barium acetate to produce 7.9 wt% BaO, and Al to produce 2.0 wt% 2 O 3A slurry of a colloidal alumina binder of 1.50 wt %, a platinum-amine complex yielding 1.32 wt % Pt, and palladium nitrate yielding 0.40 wt % Pd was applied to the substrate. After calcination at 550° C. in air for 1 hour, the washcoat loading of the bottom layer outlet zone was about 2.54 g / in 3 .
[0222] Top floor : Same as the top layer of Example 1.
[0223] Example 3: Comparative Catalytic Product C
[0224] Comparative catalytic product C has a PGM loading of 104 g / ft 3 A zoned single layer Pt / Pd / Rh catalytic article of (Pt / Pd / Rh=0 / 100 / 4) coated onto a cylindrical monolithic cordierite substrate having dimensions of 4.66" diameter and 3.81" length, a cell density of 800 cpsi and a wall thickness of 3 mils.
[0225] Entrance Area : This zone covers 50% of the substrate length from the inlet to the middle, with a PGM loading of 200 g / ft 3 (Pt / Pd / Rh=0 / 200 / 0). A mixture containing about 31.2 wt% refractory alumina, 54.6 wt% of a stable ceria-zirconia mixed oxide (OSC with about 40 wt% ceria), barium acetate yielding 7.8 wt% BaO, and ZrO yielding 1.9 wt% 2 A slurry of zirconium acetate and palladium nitrate yielding 4.51 wt% Pd was applied to the substrate. After calcination at 550°C for 1 hour in air, the washcoat loading in the inlet zone was about 2.57 g / in 3 .
[0226] Export Zone : This zone covers 50% of the substrate length from the outlet to the middle, where the PGM loading is 8 g / ft 3 (Pt / Pd / Rh=0 / 0 / 8). A composite material containing about 39.0 wt% of ceria-alumina with about 8 wt% of ceria, 54.6 wt% of a stabilized ceria-zirconia mixed oxide (OSC with about 40 wt% of ceria), 3.9 wt% of BaSO 4 , producing 0.4 wt% Al 2 O 3 of colloidal alumina binder, yielding 1.9 wt% ZrO 2A slurry of zirconium acetate and rhodium nitrate yielding 0.18 wt% Rh was applied to the substrate. After calcination at 550°C for 1 hour in air, the washcoat loading in the outlet zone was about 2.56 g / in 3 .
[0227] Example 4: Catalytic product D of the present invention
[0228] Catalytic product D of the present invention is a PGM loading of 120 g / ft 3 A zoned single layer Pt / Pd / Rh catalytic article of (Pt / Pd / Rh=29 / 87 / 4) coated onto a cylindrical monolithic cordierite substrate having dimensions of 4.66" diameter and 3.81" length, a cell density of 800 cpsi and a wall thickness of 3 mils.
[0229] Entrance area : This zone covers 50% of the substrate length from the inlet to the middle, with a PGM loading of 64 g / ft 3 (Pt / Pd / Rh=58 / 0 / 6). A composite material containing about 35.3 wt% of ceria-alumina with about 8 wt% of ceria, 56.9 wt% of a stabilized ceria-zirconia mixed oxide (OSC with about 40 wt% of ceria), 3.9 wt% of BaSO 4 , producing 0.4 wt% Al 2 O 3 colloidal alumina binder, yielding 2.0 wt% ZrO 2 A slurry of zirconium acetate, rhodium nitrate to produce 0.14 wt% Rh, and a platinum-amine complex to produce 1.32 wt% Pt was applied to the substrate. After calcination at 550°C for 1 hour in air, the washcoat loading in the inlet zone was about 2.55 g / in 3 .
[0230] Export Zone : This zone covers 50% of the substrate length from the outlet to the middle, with a PGM loading of 176 g / ft 3 (Pt / Pd / Rh=0 / 174 / 2). A mixture containing about 31.3 wt% refractory alumina, 54.9 wt% of a stable ceria-zirconia mixed oxide (OSC with about 40 wt% ceria), barium acetate yielding 7.8 wt% BaO, and ZrO yielding 2.0 wt% 2 A slurry of zirconium acetate, rhodium nitrate to produce 0.05 wt% Rh, and palladium nitrate to produce 3.95 wt% Pd was applied to the substrate. After calcination at 550°C for 1 hour in air, the washcoat loading in the outlet zone was about 2.55 g / in 3 .
[0231] Example 5: Catalytic product E of the present invention
[0232] Catalytic product E of the present invention is a PGM loading of 120 g / ft 3 A zoned Pt / Pd / Rh catalytic article of (Pt / Pd / Rh=58 / 58 / 4) coated onto a cylindrical monolithic cordierite substrate having dimensions of 4.66" diameter and 3.81" length, a cell density of 800 cpsi and a wall thickness of 3 mils.
[0233] Entrance area : This zone covers 50% of the substrate length from the inlet to the middle, with a PGM loading of 143 g / ft 3 (Pt / Pd / Rh=108 / 29 / 6). A composite material containing about 42.3 wt% of ceria-alumina with about 8 wt% of ceria, 50.2 wt% of a stabilized ceria-zirconia mixed oxide (OSC with about 40 wt% of ceria), 3.1 wt% of BaSO 4 , producing 0.3 wt% Al 2 O 3 of colloidal alumina binder, yielding 1.6 wt% ZrO 2 A slurry of zirconium acetate, rhodium nitrate to produce 0.11 wt% Rh, palladium nitrate to produce 0.53 wt% Pd, and a platinum-amine complex to produce 1.96 wt% Pt was applied to the substrate. After calcination at 550°C for 1 hour in air, the washcoat loading in the inlet zone was about 3.19 g / in 3 .
[0234] Export Zone : This zone covers 50% of the substrate length from the outlet to the middle, with a PGM loading of 97 g / ft 3 (Pt / Pd / Rh=8 / 87 / 2). A refractory ceria-alumina composite material containing about 19.2 wt% alumina, 15.3 wt% of a refractory ceria-alumina composite material having about 8 wt% ceria, 53.6 wt% of a stable ceria-zirconia mixed oxide (OSC having about 40 wt% ceria), barium acetate producing 7.7 wt% BaO, and ZrO producing 1.9 wt% 2 A slurry of zirconium acetate of 0.05 wt. % Rh, rhodium nitrate to produce 0.05 wt. % Rh, platinum-amine complex to produce 0.18 wt. % Pt, and palladium nitrate to produce 1.93 wt. % Pd was applied to the substrate. After calcination at 550° C. for 1 hour in air, the washcoat loading in the outlet zone was about 2.61 g / in 3 .
[0235] Example 6: Catalytic product F of the present invention
[0236] Catalytic product F of the present invention is a PGM loading of 120 g / ft 3 A zoned Pt / Pd / Rh catalytic article of (Pt / Pd / Rh=29 / 87 / 4) coated onto a cylindrical monolithic cordierite substrate having dimensions of 4.66" diameter and 3.81" length, a cell density of 800 cpsi and a wall thickness of 3 mils.
[0237] Entrance area, ground floor : This zone covers 50% of the substrate length from the inlet to the middle, with a PGM loading of 90 g / ft 3 (Pt / Pd / Rh=58 / 26 / 6). A composite material containing about 35.1 wt% of ceria-alumina with about 8 wt% of ceria, 56.6 wt% of a stabilized ceria-zirconia mixed oxide (OSC with about 40 wt% of ceria), 3.9 wt% of BaSO 4 , producing 0.4 wt% Al 2 O 3 of colloidal alumina binder, yielding 2.0 wt% ZrO 2 A slurry of zirconium acetate, rhodium nitrate to produce 0.14 wt% Rh, palladium nitrate to produce 0.59 wt% Pd, and a platinum-amine complex to produce 1.31 wt% Pt was applied to the substrate. After calcination at 550°C for 1 hour in air, the washcoat loading in the inlet zone was about 2.56 g / in 3 .
[0238] Top floor of the entrance area : This zone covers 31.5% of the length of the substrate from the inlet to the middle. The aluminum oxide containing about 95.3% by weight of barium doping and 4.7% by weight of Al 2 O 3 A slurry of colloidal alumina binder was coated on the bottom layer. After calcination at 550°C in air for 1 hour, the washcoat loading of the top layer of the inlet zone divided by the volume of the substrate coated by the top layer of the inlet zone was about 0.75 g / in 3 .
[0239] Export Zone : This zone covers 50% of the substrate length from the outlet to the middle, where the PGM loading is 150 g / ft 3 (Pt / Pd / Rh=0 / 148 / 2). A mixture containing about 31.5 wt% refractory alumina, 55.2 wt% of a stable ceria-zirconia mixed oxide (OSC with about 40 wt% ceria), barium acetate yielding 7.9 wt% BaO, and ZrO yielding 2.0 wt% 2A slurry of zirconium acetate, rhodium nitrate to produce 0.05 wt% Rh, and palladium nitrate to produce 3.37 wt% Pd was applied to the substrate. After calcination at 550°C for 1 hour in air, the washcoat loading in the outlet zone was about 2.54 g / in 3 .
[0240] Example 7: Catalytic Product G
[0241] Catalyst G is a PGM loading of 12 g / ft 3 A single layer Pt / Rh catalytic article of (Pt / Pd / Rh=10 / 0 / 2) coated onto a cylindrical monolithic cordierite substrate having dimensions of 5.2" diameter and 3.96" length, a cell density of 400 cpsi, and a wall thickness of 6.5 mils.
[0242] The composite material contained about 50.8 wt % of a ceria-alumina composite material having about 8 wt % ceria, 43.5 wt % of a stabilized ceria-zirconia mixed oxide (OSC having about 40 wt % ceria), barium acetate yielding 3.6 wt % BaO, barium acetate yielding 1.1 wt % ZrO 2 of zirconium acetate, yielding 0.7 wt% Al 2 O 3 A slurry of a colloidal alumina binder of 100 wt %, a platinum-amine complex to yield 0.21 wt % Pt, and rhodium nitrate to yield 0.04 wt % Rh was applied to the substrate. After calcination at 550° C. for 1 hour in air, the washcoat loading was about 2.76 g / in 3 .
[0243] Example 8: Aging and Testing of Catalytic Articles
[0244] The catalytic articles were aged for 60 hours using a 4-mode exothermic aging protocol with an effective catalyst temperature of 877° C. on an engine rig using phosphorus-doped fuel. Catalytic articles AF were installed in the close-coupled front position, while catalytic article G was installed in the close-coupled rear position. The engine-out gas feed composition was alternated between rich and lean to simulate typical vehicle operating conditions.
[0245] Emissions performance was tested using a 2.7L ULEV50 vehicle with a close-coupled tandem (front close-coupled catalyst (CCC1) / rear close-coupled catalyst (CCC2)) emission control system configuration operated according to the FTP-75 test protocol. Catalysts A, B, C, D, E, and F were tested as CCC1 catalysts, while Catalyst G was used as a common CCC2 catalyst.
[0246] During the cold start portion of the FTP-75 test, the close-coupled catalyst warms up from the heat it receives from the engine exhaust.
[0247] Figure 2 Catalyst D is shown to heat up faster than Catalyst B, likely due to the lower washcoat loading. Faster heat up is beneficial during cold start because catalytic activity is kinetically driven.
[0248] The advantages of the catalytic product of the present invention are shown in Figure 3 When tested as CCC1, Catalysts D and F of the present invention have lower tail pipe emissions than Comparative Catalysts B and C. Comparative Catalyst C has a similar carrier coating loading as Catalyst D of the present invention, indicating that the performance advantage of Catalyst D of the present invention over Comparative Catalyst C is due to catalyst design (such as carrier coating design and PGM loading / ratio) rather than a lower carrier coating loading. It was observed that Comparative Catalyst C showed the highest NOx emissions, which may be because the front zone does not contain Rh. The results show that Rh needs to be distributed throughout the catalyst to ensure good NOx performance. Comparative Catalyst B and Catalyst D of the present invention have the same PGM loading / ratio, indicating that the improvement of Catalyst D of the present invention is due to the carrier coating design. The emission performance of Catalyst F of the present invention is further improved by providing a PGM-free outer coating that protects the underlying carrier coating layer from phosphorus poisoning.
[0249] When tested as CCC1, inventive Catalyst E exhibited lower tailpipe emissions than Comparative Catalyst A. Catalyst E and Catalyst A had the same PGM loading / ratio, indicating that the improvement was due to the washcoat design.
[0250] Although the embodiments disclosed herein have been described with reference to specific embodiments, it should be understood that these embodiments are merely illustrative of the principles and applications of the invention currently claimed. It will be apparent to those skilled in the art that various modifications and variations may be made to the methods and apparatus of the invention currently claimed without departing from the spirit and scope of the invention currently claimed. Therefore, the invention currently claimed is intended to include modifications and variations within the scope of the appended claims and their equivalents, and the embodiments described above are presented for purposes of illustration and not limitation.
Claims
1. A catalytic product, comprising: a) substrate; b) a first zone, the first zone being coated with a first catalytic layer; as well as c) a second zone, said second zone being coated with a second catalytic layer, wherein the first catalytic layer comprises platinum supported on a ceria-zirconia mixed oxide or a ceria-alumina composite material or both; and rhodium supported on a ceria-zirconia mixed oxide, a ceria-alumina composite material, alumina or any combination thereof, wherein the second catalytic layer comprises palladium supported on ceria-zirconia mixed oxide, alumina, ceria-alumina composite material or any combination thereof; and rhodium supported on ceria-zirconia mixed oxide, alumina, ceria-alumina composite material or any combination thereof, The first region occupies an inflow end portion of the substrate, and the second region occupies an outflow end portion of the substrate.
2. The catalytic article of claim 1, wherein the first catalytic layer further comprises palladium supported on a ceria-zirconia mixed oxide or a ceria-alumina composite material or both.
3. The catalytic article according to any one of claims 1 to 2, wherein the second catalytic layer further comprises platinum supported on ceria-zirconia mixed oxide, alumina, ceria-alumina composites, or any combination thereof.
4. The catalytic article of any one of claims 1 to 3, wherein the total loading of the first catalytic layer and the second catalytic layer divided by the substrate volume is less than 3.2 grams per cubic inch.
5. The catalytic article according to any one of claims 1 to 4, wherein the amount of platinum in the first catalytic layer and the second catalytic layer is in the range of 0.02 wt % to 3.0 wt % based on the total weight of the first catalytic layer and the second catalytic layer, wherein the amount of palladium in the first catalytic layer and the second catalytic layer is in the range of 0.02 wt % to 5.0 wt % based on the total weight of the first catalytic layer and the second catalytic layer, and Wherein an amount of rhodium in the first catalytic layer and the second catalytic layer is in a range of 0.01 wt % to 1.0 wt % based on the total weight of the first catalytic layer and the second catalytic layer.
6. The catalytic article according to any one of claims 1 to 5, wherein the total amount of platinum supported on the ceria-zirconia mixed oxide or the ceria-alumina composite material or both in the first catalytic layer is 80 wt % to 100 wt % based on the total weight of platinum in the first catalytic layer and the second catalytic layer, wherein the total amount of palladium supported on the ceria-zirconia mixed oxide, alumina, a ceria-alumina composite material or any combination thereof in the second catalytic layer is 75 wt % to 100 wt % based on the total weight of palladium in the first catalytic layer and the second catalytic layer, and The weight ratio of rhodium loaded on cerium dioxide-zirconia mixed oxide or cerium dioxide-alumina composite material or both in the first catalytic layer to rhodium loaded on cerium dioxide-zirconia mixed oxide, alumina, cerium dioxide-alumina composite material or any combination thereof in the second catalytic layer is in the range of 1.5:1 to 4:
1.
7. The catalytic article of any one of claims 1 to 6, wherein the first zone further comprises an outer coating deposited on at least a portion of the first zone, wherein the outer coating comprises a porous refractory oxide and optionally at least one base metal oxide.
8. The catalytic article of claim 7, wherein the outer coating is substantially free of precious metals and optionally comprises an oxygen storage component.
9. The catalytic article according to any one of claims 7 to 8, wherein the length of the outer coating is equal to or less than 50% of the total length of the substrate.
10. The catalytic article of any one of claims 7 to 9, wherein the loading of the overcoat divided by the volume of the substrate coated by the overcoat is less than 1 gram per cubic inch.
11. The catalytic article according to any one of claims 7 to 10, wherein the porous refractory oxide is stabilized alumina or unstabilized alumina.
12. The catalytic article according to any one of claims 7 to 11, wherein the base metal oxide is an alkaline earth metal oxide or a rare earth metal oxide, The alkaline earth metal oxide is selected from barium oxide, magnesium oxide, calcium oxide, strontium oxide or a combination thereof. The rare earth metal oxide is at least one oxide of a rare earth metal selected from Ce, Pr, Nd, Eu, Sm, Yb and La, or a mixture thereof.
13. The catalytic article according to any one of claims 1 to 12, wherein the first zone covers 10% to 90% of the entire length of the substrate from the inflow end portion, wherein the second zone covers 10% to 90% of the entire substrate length from the outflow end portion, The first catalytic layer covers 60% to 100% of the area of the first zone, and the second catalytic layer covers 60% to 100% of the area of the second zone.
14. The catalytic article according to any one of claims 1 to 13, wherein the first zone covers 40% to 60% of the entire length of the substrate from the inflow end portion, The second zone covers 60% to 40% of the entire length of the substrate from the outflow end portion.
15. The catalytic article according to any one of claims 1 to 14, wherein the amount of the ceria-zirconia mixed oxide present in the first catalytic layer and the second catalytic layer is 40 wt% to 60 wt% based on the total weight of the first catalytic layer and the second catalytic layer.
16. The catalytic article according to any one of claims 1 to 15, wherein the amount of the aluminum oxide present in the first catalytic layer and the second catalytic layer is in the range of 5.0 wt% to 20 wt% based on the total weight of the first catalytic layer and the second catalytic layer.
17. The catalytic article according to any one of claims 1 to 16, wherein the alumina is doped with a dopant selected from barium, lanthanum oxide, zirconium oxide, neodymium oxide, yttrium oxide, ceria or titania, Wherein the amount of the dopant is 1.0 wt % to 30 wt % based on the total weight of the aluminum oxide and the dopant present in the first catalytic layer and the second catalytic layer.
18. The catalytic article according to any one of claims 1 to 17, wherein the alumina is selected from alumina, lanthanum oxide-alumina, titania-alumina, ceria-zirconia-alumina, zirconia-alumina, ceria-alumina, lanthanum oxide-zirconia-alumina, barium oxide-alumina, barium oxide-lanthanum oxide-alumina, barium oxide-lanthanum oxide-neodymium oxide-alumina or any combination thereof.
19. The catalytic article according to any one of claims 1 to 18, wherein the amount of the ceria-alumina composite material present in the first catalytic layer and the second catalytic layer is in the range of 15 wt% to 40 wt% based on the total weight of the first catalytic layer and the second catalytic layer.
20. The catalytic article according to any one of claims 1 to 19, wherein the amount of ceria calculated as CeO2 in the ceria-alumina composite material is from 5.0 wt% to 30 wt%, based on the total weight of the ceria-alumina composite material.
21. The catalytic article according to any one of claims 1 to 20, wherein the ceria-zirconia mixed oxide present in the first catalytic layer and the second catalytic layer comprises: ceria calculated as CeO2 in an amount of 15 wt% to 50 wt%, based on the total weight of the ceria-zirconia mixed oxide in the corresponding catalytic layer; and zirconium oxide calculated as ZrO2 in an amount of 50 wt% to about 85 wt%, based on the total weight of the ceria-zirconia mixed oxide in the corresponding catalytic layer.
22. The catalytic article according to any one of claims 1 to 21, wherein the ceria-zirconia mixed oxide present in the first and second catalytic layers comprises a dopant selected from lanthanum oxide, titanium oxide, hafnium oxide, magnesium oxide, calcium oxide, strontium oxide, barium oxide, yttrium, hafnium, praseodymium, neodymium or any combination thereof.
23. The catalytic article of any one of claims 1 to 22, wherein the substrate is selected from a ceramic substrate, a metal substrate, a ceramic foam substrate, a polymer foam substrate, or a woven fiber substrate.
24. A method for preparing a catalytic article according to any one of claims 1 to 23, wherein the method comprises: - preparing a composite material comprising platinum supported on a ceria-zirconia mixed oxide or a ceria-alumina composite material or both; and a first catalyst layer slurry of rhodium supported on a ceria-zirconia mixed oxide or a ceria-alumina composite material or both; - preparing a second catalytic layer slurry comprising palladium supported on ceria-zirconia mixed oxide, alumina, ceria-alumina composite material or any combination thereof; and rhodium supported on ceria-zirconia mixed oxide, alumina, ceria-alumina composite material or a combination thereof; - coating the first catalytic layer slurry on the inflow end portion of the substrate to obtain a first zone; - coating the second catalytic layer slurry on the outflow end portion of the substrate to obtain a second zone; - subjecting the substrate to calcination at a temperature ranging from 400° C. to 700° C., The step of preparing the slurry comprises a technique selected from incipient wetness impregnation, incipient wetness co-impregnation and post-addition.
25. An exhaust gas treatment system for an internal combustion engine, the system comprising the catalytic article according to any one of claims 1 to 23.
26. A method of treating a gaseous exhaust stream comprising hydrocarbons, carbon monoxide and nitrogen oxides, the method comprising contacting the exhaust stream with a catalytic article according to any one of claims 1 to 23 or an exhaust treatment system according to claim 25.
27. A method of reducing the levels of hydrocarbons, carbon monoxide and nitrogen oxides in a gaseous exhaust stream, the method comprising contacting the gaseous exhaust stream with a catalytic article according to any one of claims 1 to 23 or an exhaust treatment system according to claim 25 to reduce the levels of hydrocarbons, carbon monoxide and nitrogen oxides in the exhaust gas.
28. Use of a catalytic article according to any one of claims 1 to 23 or an exhaust gas treatment system according to claim 25 for purifying a gaseous exhaust stream comprising hydrocarbons, carbon monoxide and nitrogen oxides.